Applying anatomical optical coherence tomography to quantitative 3D imaging of the lower airway - McLaughlin, R.; Williamson, J.; Phillips, M.; Armstrong, J.; Becker, S.; Hillman, D.; Eastwood, Peter; Sampson, D. (Optical Society of America, 2008)
Endoscopic treatment of lower airway pathologies requires accurate quantification of airway dimensions. We demonstrate the application of a real-time endoscopic optical coherence tomography system that can image lower airway anatomy and quantify airway lumen dimensions intra-operatively. Results demonstrate the ability to acquire 3D scans of airway anatomy and include comparison against a pre-operative X-ray CT. The paper also illustrates the capability of the system to assess the real-time dynamic changes within the airway that occur during respiration. © 2008 Optical Society of America.